2006
DOI: 10.1016/j.apcata.2006.03.007
|View full text |Cite
|
Sign up to set email alerts
|

CO adsorption on the surface of MgO(001) thin films

Abstract: We report infrared reflection-absorption and thermal desorption spectra of CO adsorbed at low temperature (30 K) on the surface of MgO(001) thin films. The high similarity of the observed IR bands as compared to data reported for MgO(100) single crystals and sintered MgO particles gives evidence for the identical surface morphology of the different substrates. CO adsorption series taken at constant temperature/ variable pressure, variable temperature/constant pressure, as well as isotope mixing experiments rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…The adsorption of carbon monoxide on the MgO(001) surface has been extensively studied both experimentally [32][33][34] and theoretically [27][28][29][30] in the last 20 years. At low coverage CO adsorbs in a C-down configuration on top of Mg 2þ 5c surface sites.…”
Section: Adsorption Of Carbon Monoxide On Magnesium Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption of carbon monoxide on the MgO(001) surface has been extensively studied both experimentally [32][33][34] and theoretically [27][28][29][30] in the last 20 years. At low coverage CO adsorbs in a C-down configuration on top of Mg 2þ 5c surface sites.…”
Section: Adsorption Of Carbon Monoxide On Magnesium Oxidementioning
confidence: 99%
“…After a brief outline of the theory in the next section and a discussion of the changes of dispersion in ionic systems, we will present as examples results for adsorption of acetylene on sodium chloride and carbon monoxide on magnesium oxide. These prototypical systems have been investigated previously by theoretical [27][28][29][30][31] and experimental [32][33][34][35][36][37] techniques.…”
mentioning
confidence: 99%
“…2.6c). A CO-TPD taken after annealing to 1,200 K shows that the high-temperature desorption signals can be significantly reduced by thermal ordering of the thin film surface [66], providing support for the assignment of these desorption features to more strongly bound CO on low-coordinated sites. An analysis of the desorption energy of CO on MgO(100) thin film surfaces based on inversion of the Wigner-Polanyi equation is presented in Fig.…”
Section: Adsorption On Low-coordinated Sitesmentioning
confidence: 95%
“…The value for 5C sites is in good agreement with desorption energies derived from CO-TPD studies of vacuumcleaved MgO single-crystals, where CO was found to desorb in a single peak at 57 K, yielding E des = 15.2 kJ/mol by using the Redhead analysis [64]. Different to MgO (100) single-crystals, the CO-TPD data for as-deposited MgO(100)/Mo(100) thin films exhibit two distinct desorption maxima of almost equal intensity at 52 and 68 K, and further desorption signals extending up to *100 K [62,[65][66][67], suggesting a high abundance of low-coordinated sites on the surface (Fig. 2.6c).…”
Section: Adsorption On Low-coordinated Sitesmentioning
confidence: 97%
See 1 more Smart Citation